Histone Deacetylase Inhibitor Scriptaid Alleviated Neurological Dysfunction after Experimental Intracerebral Hemorrhage in Mice - Heng Yang; Wei Ni; Hanqiang Jiang; Yu Lei; Jiabin Su; Yuxiang Gu; Liangfu Zhou (Behavioural Neurology)
Objectives. To investigate the role of Scriptaid in reducing brain injury after intracerebral hemorrhage (ICH) in mice. Methods. An ICH model was constructed by injecting autologous blood into the right basal ganglia in mice. The animals were administered 3.5 mg/kg of Scriptaid intraperitoneally after ICH. The hematoma volume and hemoglobin level were measured to examine hematoma resolution. A behavior test and brain edema and white matter injury examinations indicated brain injury after ICH. Results. Scriptaid treatment promoted hematoma resolution and reduced the hematoma volume 7 d after ICH compared with the vehicle group (P<0.05). Scriptaid treatment also alleviated the brain water content in the ipsilateral basal ganglia (P<0.05) and cortex (P<0.01) 3 d after ICH. In addition, Scriptaid improved neurological function recovery and alleviated white matter injury 35 d after ICH. Conclusions. Scriptaid can protect against brain injury after ICH and may be considered a new medical therapy method for ICH.